Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 11 - Additional Topics - Chapter 11 Test - Page 521: 5



Work Step by Step

Multiplying each term of the first expression with the whole the second expression to simplify, we obtain: $(3+i)(2-5i)$ =$3(2-5i)+i(2-5i)$ =$6-15i+2i-5i^{2}$ =$6-15i+2i-5(-1)$ (as $i^{2}=-1$) =$6-15i+2i+5$ =$6+5-15i+2i$ =$11-13i$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.